2020
DOI: 10.26444/aaem/105927
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and biochemical predictors of late-outcome in patients after ischemic stroke

Abstract: Objective. The aim of this study is to evaluate neurological scales, as well as biochemical and radiological parameters measured on day 10 after ischemic stroke (IS), according to their value as predictors of the long-term outcome. Materials and method. 45 patients were assessed according to the Barthel Index (BI) and National Institute of Health Stroke Scale (NIHSS) on day 10, and according to Modified Rankin Scale (mRS) 3 months after the onset of IS. On day 10 of IS, the serum level of C-reactive protein (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Aged stroke patients may have higher mortality, longer hospital stay, and poorer quality of life than their younger counterparts [ 35 ]. Bielewicz et al [ 6 ] reported that the BI scores assessment on day 10 was predictive of outcomes 3 months after ischemic stroke onset, indicating that the preexisting functional status was positively correlated with the prognosis of stroke patients. Besides, the NIHSS score has been shown to reflect neurological deficits and is considered valuable for predicting the outcome of stroke patients [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Aged stroke patients may have higher mortality, longer hospital stay, and poorer quality of life than their younger counterparts [ 35 ]. Bielewicz et al [ 6 ] reported that the BI scores assessment on day 10 was predictive of outcomes 3 months after ischemic stroke onset, indicating that the preexisting functional status was positively correlated with the prognosis of stroke patients. Besides, the NIHSS score has been shown to reflect neurological deficits and is considered valuable for predicting the outcome of stroke patients [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…The variables were screened based on previously published articles and clinical experience [ 6 , 11 , 20 ]. Accordingly, 25 clinical variables were used in this study, and the data of the 216 patients were randomly divided into training (n = 168, 80%) and test (n = 48, 20%) sets using the Kennard-Stone algorithm.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations